QUALITY OF LIFE AMONG LOWER LIMB PROSTHESIS USERS ATTENDING ARTIFICIAL LIMB CENTER OF FAUJI FOUNDATION HOSPITAL RAWALPINDI: Prosthesis Users And Quality of Life - Amjad, Dr Tahira; Umay Kalsoom, Umay Kalsoom; Bairam, Saima (Pakistan Armed Forces Medical Journal, 2018)
Objective: To assess quality of life and the influencing factors as perceived by lower limb prosthesis users. Study Design: Cross sectional study. Place and Duration of Study: Artificial Limb Centre, Fauji Foundation Hospital Rawalpindi, 11 months (Jan to Nov 2014). Material and Methods: A sample of 50 patients with lower limb amputations and using lower limb prosthesis were recruited by applying inclusion criteria. Responses were recorded on demographic variables, reasons for amputation, time of provision of prosthesis, employment status etc. by the investigator on a structured pretested questionnaire after their consent. A p-value of <0.05 was taken as significant. Quality of life was interpreted on 5 point Likert scale. Data was analyzed in SPSS version 21. Result: Majority of respondents i.e. 17 (34%) were in 51-60 years age group with mean age 46 ± 14 years while 33 (66%) were males and 27 (54%) illiterate, 33 (66%) could afford a prosthesis. Trauma 28 (56%) was the most prevalent cause of lower limb amputation and among them 15 (53%) had road accident injuries. Various factors influenced quality of life as perceived by the respondents and in 10 (20%), 16 (32%), 25 (50%) social, family life and emotional status was affected respectively, while 14 (28%) of the prosthesis user were unemployed. Prosthesis were provided after 2 years in 18 (36%) and in 37 (74%) prosthesis were provided by the health care facility. Good quality of life was perceived in 40 (80%) respondents. Conclusion: Perceived Quality of life was good in majority of the prosthesis users but others can’t be ignored. It can be improved by early provision of prosthesis which can help in better employment opportunities.